UJI EFEKTIVITAS KULIT BUAH KAKAO (Theobroma cacao L.) SEBAGAI ANTIDIABETIK - Muhamad Reza Iskandar; Gita Julianti Malik; Violata Advenia Dae; Cindy Dwi Lestari Dwi Lestari; I Putu Sudayasa (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
Cocoa fruit peels have great potential and can be used as a renewable source of natural antioxidants. Previously, there has been no further research on clinical trials of the antioxidant potential present in the skin of cocoa fruit (Theobroma cacao L.) about what side effects will be caused if the substance enters the body. Therefore, researchers want to develop a test of the effectiveness of cocoa fruit skin (Theobroma cacao L.) through clinical trials using animal tests (Rattus novergicus) induced Streptozotosin. provide the latest research results through clinical trials of cocoa fruit skin waste and develop cocoa fruit research (Theobroma cacao L.) especially its potential to increase the Southeast Sulawesi region in developing cocoa fruit as a superior commodity. This research is done by making cocoa fruit skin waste extract (Theobroma cacao L.) by maceration method using acetone solvent 2.5 L. Next, divide the test animals into 4 experimental groups. Group 1 was a normal mouse, group 2 was a mouse given streptozotosin and Na-CMC 0.5%, Group 3 was the group given streptozotosin and metformin. Group 4 is the group given streptozotosin and cocoa fruit peel extract (Theobroma cacao L.). The results of this study prove that flavonoid compounds contained in cocoa fruit skin waste (Theobroma cacao L.) have a role in lowering blood glucose levels in test animals.Cocoa fruit skin waste extract (Theobroma cacao L.) has been shown to lower the glucose levels of test animals (Rattus novergicus)